The Impact of Clinical Pharmacist Interventions on Medication Errors Management in the Postoperative Cardiac Intensive Care Unit - Naser Safaie; Hanieh Azizi; Sajad Khiali; Taher Entezari-Maleki (Tabriz University of Medical Sciences, 2021)
Background: Medication errors (MEs) frequently occur in intensive care unit (ICU) admittedpatients. The present study aimed to evaluate the frequency and types of MEs in an open heartsurgery heart ICU and clinical pharmacists' role in the management of them. Methods: This cross-sectional, observational study was performed from October 2016 toMarch 2017 in the Shahid Madani Heart Center. A clinical pharmacist reviewed patients' files,laboratory data, and physician orders during morning hours. All of the MEs and the clinicalpharmacies' recommendations for the management of them were analyzed. Results: A total of 311 MEs were observed in the medical files of 152 patients. The rate of MEswas 2.04 errors per patient and 0.19 errors per ordered medication. The acceptance rate of MEswas 72.6%. The most type of MEs was 'forgot to order' (75 cases, 24.1%) followed by "wrongfrequency" and "adding a drug" in 56 (18%) and 49 (15.8) patients, respectively. Most MEs wereinsignificant. Conclusion: MEs occur at different stages of the therapeutic process in the postoperative cardiacintensive care unit, and clinical pharmacists play an essential role in detecting and managingMEs.